Boost the Lead Conversion Efficiency for the Synthesis of Colloidal 2D PbS Nanosheets. Issue 3 (30th December 2022) - MDS Weeraddana, Tharaka; Roach, Adam; Premathilaka, Shashini M.; Tang, Yiteng; Fox, Jordan; Sun, Liangfeng
Abstract : In the synthesis of colloidal PbS nanosheets, the supernatant of the reaction solution is reused to boost the lead conversion efficiency. It doubles the conversion efficiency of the lead precursors to the PbS nanosheets. The nanosheets synthesized by reusing the supernatant have similar morphology, nearly identical thickness, and optical properties as the original ones, confirmed by transmission electron microscopy, X‐ray diffraction, and photoluminescence spectroscopy. This method reduces the toxic Pb‐containing waste during the synthesis, a step toward the green and scalable synthesis of colloidal 2D PbS nanosheets. Abstract : By reusing the reaction supernatant, the lead conversion efficiency is nearly doubled for the synthesis of colloidal PbS nanosheets. Synthesized nanosheets have well‐controlled thickness and optical properties, confirmed by transmission electron microscopy, X‐ray diffraction, and photoluminescence spectroscopy. It is a step toward a green and scalable synthesis of this 2D material for infrared applications.